Kritik Terhadap Sekularisme (Pandangan Yusuf Qardhawi) - Ismail, M. Syukri (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Since theÂ first appearanceÂ untilÂ now,Â secularismÂ had attractedÂ the attention of manyÂ people: scientists,Â theologians, Â clergy, thinkers, and also by groups of religious studies. Due to theÂ understandingÂ hadÂ containsÂ manyÂ irregularities,Â especially ifÂ this understandingÂ entered toÂ IslamicÂ ideology.Â Because secularism Â wasÂ understoodÂ thatÂ was believed comeÂ fromÂ the Â WestÂ not fromIslamicÂ culture.Â AlreadyÂ soÂ manyÂ scholars, Â scientists,Â andÂ thinkersÂ whoÂ devotedÂ criticalÂ attentionÂ to Â secularism,Â one ofÂ them wasÂ Yusuf Qardhawi,Â who had a very goodÂ opinioninÂ IslamÂ rules,Â heÂ was consideredÂ as a classicÂ of Â scienceÂ andÂ aÂ modern masterÂ inÂ Islam,Â QardhawiâsÂ criticism againstÂ secularismÂ based onunderstanding of Islam.Â Based on Â theÂ explanationÂ above,Â the authorsÂ wanted to examineÂ Yusuf Â QaradawiâsÂ criticismÂ againstÂ secularism,Â andÂ in particular issues thatÂ wouldbe discussed:Â the problemsÂ ofÂ Qardhawiâs criticismÂ againstÂ secularism,Â the reasonsÂ ofÂ QardhawiÂ in criticizingÂ secularism,Â and theÂ solutionÂ that wasgiven in facing of secularism.